2020
DOI: 10.1002/ece3.7126
|View full text |Cite
|
Sign up to set email alerts
|

Freezing in a warming climate: Marked declines of a subnivean hibernator after a snow drought

Abstract: Recent snow droughts associated with unusually warm winters are predicted to increase in frequency and affect species dependent upon snowpack for winter survival. Changes in populations of some cold‐adapted species have been attributed to heat stress or indirect effects on habitat from unusually warm summers, but little is known about the importance of winter weather to population dynamics and how responses to snow drought vary among sympatric species. We evaluated changes in abundance of hoary marmots (Marmot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 101 publications
0
9
0
Order By: Relevance
“…Ozgul et al, 2010). For example, in other snow-dominated mountain ecosystems, population abundance of small mammals was most strongly affected by winter conditions compared with other alternative mechanisms, including resource availability and phenology (Johnston et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ozgul et al, 2010). For example, in other snow-dominated mountain ecosystems, population abundance of small mammals was most strongly affected by winter conditions compared with other alternative mechanisms, including resource availability and phenology (Johnston et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…For example, abiotic factors, such as short winters or hot summers, might exert stronger effects on certain parts of an organism's life cycle compared with other stages, where biotic factors, such as food resources, may prevail instead (e.g. Johnston et al, 2021; Radchuk et al, 2013). Nevertheless, the effects of abiotic and biotic factors on different parts of an organism's life cycle are often not accounted for, which limits our understanding of the effects of environmental variation on populations (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…It should be noted that this sequential approach ignores uncertainty in behavioral classifications, whereas a joint approach which directly propagates uncertainty between models would be better suited to deal with such issues. While a major focus of conservation efforts is providing breeding and foraging habitat, areas of respite from inclement winter weather can be equally important for individual fitness (Johnston et al, 2021;Shipley et al, 2020). For resident individuals in temperate climates, conservation of winter shelter should be considered in conservation assessments (Greiser et al, 2020;Keppel et al, 2012Keppel et al, , 2015.…”
Section: Changing Temperate Ecosystemsmentioning
confidence: 99%
“…Furthermore, Johnston et al (2019) found drastic declines in pika abundances the year following a snow drought, which led to a functionally colder winter (i.e., less snowpack reduced thermal buffering from fluctuating above‐snow temperatures). This relationship between warmer winter conditions and cold stress may seem paradoxical; however, recent investigations of other species that occupy similar habitats as pikas, yellow‐bellied marmots ( Marmota flaviventris ) and hoary marmots ( Marmota caligata ), have documented declines in population size and over‐winter survival in response to lower snowpack since both species require sufficient snow for thermal insulation while hibernating (Cordes et al, 2020; Johnston et al, 2021). Such investigations exemplify how cold‐adapted species like pikas are excellent indicator species for both quantifying the direct and indirect effects of climate change and illustrating sensitivity to short‐term weather conditions (but see Smith & Millar, 2018, who used site occupancy as a proxy for over‐winter survival at n = 37 patches).…”
Section: Methodsmentioning
confidence: 99%